Cucuk Lampah: Cooperative Principles Violations to Create Laughter at Wedding Ceremony in Magetan - Mubarokah, Qoniatul; Djatmika, Djatmika; Sumarlam, Sumarlam (Bina Nusantara University, 2019)
This research aimed at describing the violations of cooperative principles and the factors that created humor of Cucuk Lampah in the wedding ceremony in Magetan regency. This was descriptive qualitative research. The subjects of this research were all humor discourse conducted by Cucuk Lampah. Meanwhile, the objects were the data that contained the violation of the cooperative principle. The data collection used observation method with the tapping technique, then SBLC or Free Participant Observation technique, note-taking technique, and video recording technique. It used a pragmatic identity method based on utterances by heuristic technique to analyze data. The result shows that in creating humor, Cucuk Lampahmostly violates quantity maxim. It means that Cucuk Lampah prefers less and more information or contribution to the interaction. Cucuk Lampah is free to lie, using taboo, speaking indirectly with pambiwara, and singers. Cucuk Lampah also uses language play by mentioning the unexpected in the utterances to build up taboo words. The violations of the quality maxim, relevance maxim, and manner maxim are also done in less number compare to quantity maxim violations. The nonobservance of the maxims mostly is violating a maxim, flouting a maxim, infringing a maxim, suspending a maxim, and the last is opting out of a maxim